Fragment‐based discovery of flexible inhibitor targeting wild‐type acetohydroxyacid synthase and P197L mutant. Issue 10 (25th January 2020) - Qu, Ren‐Yu; Yang, Jing‐Fang; Chen, Qiong; Niu, Cong‐Wei; Xi, Zhen; Yang, Wen‐Chao; Yang, Guang‐Fu
Abstract: BACKGROUND: Intensifying weed resistance has challenged the use of existing acetohydroxyacid synthase (AHAS)‐inhibiting herbicides. Hence, there is currently an urgent requirement for the discovery of a new AHAS inhibitor to effectively control AHAS herbicide‐resistant weed species produced by target mutation. RESULTS: To combat weed resistance caused by AHAS with P197L mutation, we built a structure library consisting of pyrimidinyl‐salicylic acid derivatives. Using the pharmacophore‐linked fragment virtual screening (PFVS) approach, hit compound 8 bearing 6‐phenoxymethyl substituent was identified as a potential AHAS inhibitor with antiresistance effect. Subsequently, derivatives of compound 8 were synthesized and evaluated for their inhibitory activities. The study of the enzyme‐based structure–activity relationship and structure−resistance relationship studies led to the discovery of a qualified candidate, 28 . This compound not only significantly inhibited the activity of wild‐type Arabidopsis thaliana ( At ) AHAS and P197L mutant, but also exhibited good antiresistance properties (RF = 0.79). Notably, compared with bispyribac at 37.5–150 g of active ingredient per hectare (g a.i. ha –1 ), compound 27 exhibited higher growth inhibition against both sensitive and resistant Descurainia sophia, CONCLUSION: The title compounds have great potential to be developed as new leads to effectively control herbicide‐resistant weeds comprising AHAS with P197L mutation. Also, our study provided a positive case for discovering novel, potent and antiresistance inhibitors using a fragment‐based drug design approach. Abstract : A series of pyrimidinyl‐salicylic derivatives 8 –28 were designed and synthesized via a pharmacophore‐linked fragment virtual screening approach in the Auto Core Fragment in silico Screening server. Compound 28 with high potency was identified as a promising antiresistance acetohydroxyacid synthase inhibitor. © 2020 Society of Chemical Industry